The advent of unholy alliances? Coalition governments in the aftermath of disputed elections and electoral violence in Africa : a case study of Kenya - Steytler, N.C. (Nico) (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.